2017
DOI: 10.1097/j.pain.0000000000001092
|View full text |Cite
|
Sign up to set email alerts
|

Preschool children's coping responses and outcomes in the vaccination context: child and caregiver transactional and longitudinal relationships

Abstract: This article, based on 2 companion studies, presents an in-depth analysis of preschoolers coping with vaccination pain. Study 1 used an autoregressive cross-lagged path model to investigate the dynamic and reciprocal relationships between young children's coping responses (how they cope with pain and distress) and coping outcomes (pain behaviors) at the preschool vaccination. Expanding on this analysis, study 2 then modeled preschool coping responses and outcomes using both caregiver and child variables from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
(49 reference statements)
3
18
0
Order By: Relevance
“…This finding supports our second hypothesis, and makes a novel contribution to our understanding of the mechanisms through which parent behaviors influence infant acute pain outcomes. It also replicates findings from previous studies that identified stronger relationships between parent distress-promoting behaviors (when compared with coping-promoting behaviors) and pain-related distress in in preschoolers [ 19 ] and older children [ 20 , 21 ]. Taken together, these findings suggest that teaching parents to avoid engaging in suboptimal behaviors may be more impactful than solely emphasizing optimal behaviors in the management of vaccination pain.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This finding supports our second hypothesis, and makes a novel contribution to our understanding of the mechanisms through which parent behaviors influence infant acute pain outcomes. It also replicates findings from previous studies that identified stronger relationships between parent distress-promoting behaviors (when compared with coping-promoting behaviors) and pain-related distress in in preschoolers [ 19 ] and older children [ 20 , 21 ]. Taken together, these findings suggest that teaching parents to avoid engaging in suboptimal behaviors may be more impactful than solely emphasizing optimal behaviors in the management of vaccination pain.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, we found that emotional availability made negligible contributions to pain outcomes when other aspects of parent behaviors were put in the model. While previous work with the OUCH cohort identified relationships between emotional availability and pain outcomes, these studies did not examine the concurrent contributions of emotional availability in the context of other parent factors [ 14 , 15 , 19 ]. Given that many of the behaviors accounted for by our measure of distress-promoting behaviors are reflective of a low degree of emotional attunement between parent and infant, and can, therefore, be conceptualized as being indicative of parent insensitivity, our finding is not surprising.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, researchers have recommended parents are explicitly discouraged from using distresspromoting behavior (during needle-related procedures) (Campbell, DiLorenzo, et al, 2017;Campbell, Pillai Riddell, Cribbie, Garfield, & Greenberg, 2017;Pillai Riddell et al, 2017). This recommendation stems from findings that suggest reducing parental distress-promoting behavior is more important for child coping outcomes than increasing parental coping-promoting behavior .…”
Section: Parenting Interventions For Procedural Distressmentioning
confidence: 99%